University Tax Centres Role: A perspective of The Slippery Slope Theory - Norbertus Purnomolastu; Dian Anita Nuswantara; Lintang Venusita; Nirma Kurriwati; Yuni Khoirotul Abdiyah (Jurnal Perpajakan dan Keuangan Publik, 2026)
Written briefly in English and Indonesian in one paragraph of 150-300 words, Small and Medium Enterprises (SMEs) are vital economic contributors, yet their tax compliance remains a persistent challenge due to systemic and resource-based barriers. This research aims to explore the multifaceted reasons behind SME tax non-compliance and analyze the strategic role of university tax centers in addressing these issues. Adopting a qualitative approach, semi-structured interviews were conducted with 15 key informants in Surabaya, Indonesia, including taxation lecturers, SME owners, and financial department heads. The results reveal that SME non-compliance is primarily driven by a lack of tax awareness, legal complexity, distrust in government institutions due to perceived corruption, and prevailing social norms of tax avoidance. University tax centers effectively mitigate these challenges by providing targeted educational programs, personalized consulting services, and acting as trusted intermediaries to bridge the gap between taxpayers and authorities. This study concludes that university tax centers are pivotal in fostering a sustainable culture of compliance and reducing administrative burdens for the SME sector. The research contributes to the Slippery Slope Theory by demonstrating how academic institutions can prevent the escalation of non-compliance through early intervention and informed support, offering a novel institutional perspective on SME tax behavior.